PARTISIPASI MASYARAKAT SEBAGAI AMANAT KONSTITUSI DALAM RANGKA MENINGKATKAN MASYARAKAT PATUH HUKUM DALAM PERSPEKTIF UNDANG-UNDANG NOMOR 22 TAHUN 2009 - Gokma Toni Parlindungan S (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2018)
The purpose of this study was to determine how the condition of traffic safety and the level of compliance with the law society today, to determine the factors that influence the condition of traffic safety and the level of compliance with the laws of society and to find out how the conception of strategic law enforcement that can improve traffic safety cross and legal compliance community. This research is descriptive and views of its objectives including empirical legal research. Data used include primary data and secondary data. Data collection through interviews and research of literature both books, legislation, papers, results of previous studies, documents and so on. Analyzed using kualitatif. This study, the result that traffic accidents in the city of Indonesia can be drawn from the data within the last 10 years show that traffic accidents that occurred in the city of Indonesia has claimed lives an average of 10,000 per year. The cause of the accident that occurred is dominated by the human factor, vehicle, road factors, and environmental factors. So for the purpose of creating a community of law-abiding in order to realize Kamseltibcar So we need a strategy that one of them is carrying out management and traffic engineering tailored to available funding and create law enforcement oriented towards changing traffic situations in realizing the security situation order and smoothness traffic both from the driver, vehicle, road and environment.